I have a problem, solve for x.
ln(x+2)-2ln(3)=0 ln(x+2)-2ln3=0
So I guess 2ln(3)=2ln
But first I did this because I didn't notice the second equation.
ln(x+2)=2ln(3)
[e^(2ln(3)]=x+2
x=[e^2ln(3)]-2
What do you think?
I have a problem, solve for x.
ln(x+2)-2ln(3)=0 ln(x+2)-2ln3=0
So I guess 2ln(3)=2ln
But first I did this because I didn't notice the second equation.
ln(x+2)=2ln(3)
[e^(2ln(3)]=x+2
x=[e^2ln(3)]-2
What do you think?
Your solution to solve $\displaystyle \ln(x+2)-2\ln(3)=0$ is fine, but you can simplify it this way:
$\displaystyle \ln(x+2)=2\ln(3)$
$\displaystyle \Leftrightarrow \ln(x+2)=\ln(9)$
and therefore
$\displaystyle x+2=9 \Leftrightarrow x=7$
Also notice: $\displaystyle e^{\ln(x)}=x$
But this statement:
$\displaystyle 2\ln(3)=2\ln$
doesn't make sense ... the two given equations are totally equal.